Prevalence of celiac disease in patients with short stature: A systematic review and meta‐analysis. Issue 1 (23rd August 2020) - Singh, Achintya D; Singh, Prashant; Farooqui, Naba; Strand, Tor; Ahuja, Vineet; Makharia, Govind K
Abstract: Background and Aim: Short stature is a common extraintestinal manifestation of celiac disease (CeD). We conducted a systematic review and meta‐analysis to assess the global prevalence of CeD in patients presenting with short stature. Methods: We searched Medline and EMBASE databases for the keywords "celiac disease, coeliac disease, anti‐gliadin, tissue transglutaminase antibody, anti‐endomysial antibody, short stature and growth retardation." All the studies published from January 1991 to May 2020 were included. Patients without any prior evaluation for short stature were classified as all‐cause short stature, while prior evaluated patients, where no cause was found for short stature, were classified as idiopathic short stature. The diagnosis of CeD was based on the European Society for Paediatric Gastroenterology, Hepatology and Nutrition guidelines. A random‐effects model was used to pool the data. Results: Seventeen studies screening 3759 patients (1582 with all‐cause short stature and 2177 with idiopathic short stature) were included. The pooled seroprevalence of CeD based on positive anti‐tissue transglutaminase antibody and anti‐endomysial antibody was 11.2% (95% CI 4.0–21.2%; I 2  = 86%) and 9.7% (95% CI 2.7–20.2%; I 2  = 95%) for all‐cause and idiopathic short stature, respectively. Similarly, pooled prevalence of biopsy‐confirmed CeD was 7.4% (95% CI 4.7–10.6%; I 2  = 76%) and 11.6% (95% CI 4.1–22.2%; I 2  = 97%), for all‐cause and idiopathic short stature, respectively. There was an overall severe risk of selection bias and significant heterogeneity in the pooled results. Conclusions: Approximately one in 14 patients with all‐cause short stature and one in nine patients with idiopathic short stature had biopsy‐confirmed CeD. Therefore, evaluation for CeD may be prudent in all patients with short stature.